2014
DOI: 10.20344/amp.5100
|View full text |Cite
|
Sign up to set email alerts
|

Aterosclerose Carotídea e Hipodensidades da Substância Branca: uma Relação Controversa

Abstract: Introduction:White matter hypodensities of presumed vascular origin, are recognized as an important cause of morbidity with established clinical and cognitive consequences. Nonetheless, many doubts remain on its physiopathology. Our goal is to clarify the potential role of carotid atherosclerosis and other vascular risk factors in the development of white matter hypodensities of presumed vascular origin. Material and Methods:We included patients that underwent CT brain scan and neurosonologic evaluation within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In a large population-based study, the periventricular but not deep WMLs were significantly associated with an increased number of plaques in the carotid artery (20). On the other hand, several studies found no relation between carotid atherosclerosis and white matter lesions (15, 16). For example, Potter et al found no association between ipsi- or contralateral ICAS and WMLs, before or after adjusting for other risk factors and suggested that the association between ICAS and WMLs are due to these underlying risk factors (15).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In a large population-based study, the periventricular but not deep WMLs were significantly associated with an increased number of plaques in the carotid artery (20). On the other hand, several studies found no relation between carotid atherosclerosis and white matter lesions (15, 16). For example, Potter et al found no association between ipsi- or contralateral ICAS and WMLs, before or after adjusting for other risk factors and suggested that the association between ICAS and WMLs are due to these underlying risk factors (15).…”
Section: Discussionmentioning
confidence: 96%
“…Another pathophysiological mechanism explaining this association came from animal models with induced ICAS, where chronic hemodynamic impairment caused the delayed development of WMLs (13, 14). On the other hand, several studies found no relation between ICAS, and WMLs, and hence it was suggested that both are the result of the underlying risk factors like age or hypertension (15, 16). To explain these contradicting results, we speculate that special characteristics related to the ICAS might be related to the WMLs and hence in absence of these characteristics, ICAS would not be associated with WMLs.…”
Section: Introductionmentioning
confidence: 99%